The Influence of Perceived Social Media Marketing Activities, Brand Trust, Brand Experience and Brand Love to Purchase Intention Case Study Indonesian Traditional Cake - Elisabeth Santy Paskalisa; Daniel Hamonangan Aruan (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the role of social media marketing activities (PSMMA) in promoting Indonesian traditional cakes through brand trust, brand experience, brand love, and purchase intention. Social media is considered an important tool to preserve and increase public interest in traditional cake products. Design/methodology/approach – This research used a quantitative method with questionnaire data collected from 300 social media users familiar with Monamy Bakery, Sari sari Aneka Jajan Pasar, and Holland Bakery. The study analyzed the relationships among social media marketing activities, brand trust, brand experience, brand love, and purchase intention. Findings/Results – The results show that interactivity, informativeness, entertainment, and perceived relevance positively affect brand trust. Brand trust also has a positive effect on brand experience and brand love, which further influences purchase intention. The strongest relationship was found between brand trust and brand love. Originality/Value – This study emphasizes the importance of social media marketing in building trust and emotional attachment toward traditional cake brands. The findings suggest that effective social media content can increase consumer interest and purchase intention for traditional culinary products.